PM.40 Lifestyle Intervention Reduces the Need For Insulin Therapy and Macromia in Gestational Diabetes Mellitus. (26th April 2013) - Walsh, CE; Coffey, M; Daniel, U; Byrne, E; Gavin, C; Firth, R; McAuliffe, F; Foley, M
Abstract : Introduction: In 2011 "life style intervention" was introduced in addition to a low glycaemic diet and insulin (when required), for management of patients diagnosed with gestational diabetes (GDM) at the National Maternity Hospital. Methods: A prospective study of the potential benefit of lifestyle intervention versus standard management in the treatment of gestational diabetes mellitus. Lifestyle management included group education on diet and exercise and a personal glucometer for home blood sugar monitoring, reinforced at least weekly contact with the diabetic team. Data on demographics, insulin use and macrosomia was collected. Results: In the period 2008–2010, 412 cases with GDM received standard management and from 2011 onwards, data was available on 353 cases of GDM following the introduction of life style intervention. Patient demographics were similar in both groups and there was no significant difference in mean age, BMI, gestational weight gain and ethnicity between the two groups. In the pre-intervention cohort, 40.7% (168/412) were treated with insulin, compared with 22% (78/353) post intervention (p < 0.001).The incidence of macrosomia (birth weight >90% centile for gestational age) was 20% prior to 2011 (84/412) and 13.8% (49/353) following intervention (p < 0.04) (Table 1 ). Conclusion: The results show that the intervention has almost halved the need for insulin treatment in patients with GDM without any compromise in fetal outcome. The results strongly suggest that a randomised trail of life style intervention should be conducted.